Pliocene and Quaternary environmental change in Kashmir, north-west Himalaya - Holmes, J; Holmes, Jonathan Anthony (1989)
﻿ Late Cainozoic environmental changes in Kashmir (33°30' to 34°30' N: 74°10' to 75°30' E) have been reconstructed using a range of techniques. The sedimentary record in Kashmir consists of a thick (>1000m) basin-fill sequence known as the Karewa group, together with glacial and related sediments in the surrounding mountain flanks. The Karewa sediments are fluviolacustrine in origin and comprise alternations of conglomerates, sands and clayey silts. Work on the lower Karewa formation, which has previously been dated palaeomagnetically to between 4 and 0.4 MaBP, involved the semi- quantitative analysis of clay-mineral assemblages by X-ray diffraction.The clay minerals in the lower Karewa mudstones are interpreted as detrital clays which reflect weathering within Kashmir basin. The analyses showed a change in clay mineralogy between about 2.5 and 2.3MaBP, from abundant kaolinite to abundant smectite. Work on the upper Karewa formation involved field description and mapping of facies, sedimentological analysis, dating using thermoluminescence (TL) and amino-acid racemization, and analysis of ostracod assemblages from lacustrine sediments. Areal restriction of the lake in Kashmir occurred about 0.4MaBP with the rapid uplift of the Pir Panjal Range. Sedimentological data show that aeolian dust formed a major input into the lake. Ostracod assemblages show that the lake itself was cool, shallow, alkaline and had abundant plant macrophytes, The lake drained between 120 and SOkaBP. Stratigraphical, sedimentological and faunal evidence suggests that this was a result of tectonically-induced drainage rather than climatically-induced desiccation. The glacial history of the surrounding mountain flanks was reconstructed by field mapping of glacial sediments and dated using TL and radiocarbon methods. Present and past patterns of glaciation wore assessed by the determination of equilibrium-line altitudes (ELAs), glaciation thresholds (GTs) and cirque aJtitudes. Glaciers extended to 2150 m a.s.l in the Great Himalayan flank and 2600 m a.s.l. in the Pir Panjal. There is evidence for only 2 pre-Holucene advances in Kashmir, the older of which predates 35kaBP. Present patterns of glacierization indicate a SW to NE rise in the height of ELAs and GTs suggesting topographic and precipitation control. An apparent reversal of trends during the past is explained by Quaternary uplift of the Pir Panjal Range.